(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article considers the relevance of the field of translation, the need to systematize the various and sometimes conflicting studies in the field, as well as to identify the scientific gaps that need to be filled in the translation paradigm. Also, the main approaches to the study of the main concepts of translation studies using the methods of summarizing and interpreting the results were determined: comparative-transformational and communicative-functional, “linguistic barrier”, “equivalence”, “untranslatability”, “linguistic-cultural adaptation strategies of the text” were studied as the main concepts relevant for the study of the “culture” factor in translation.